Pengembangan Video Tutorial Pembuatan Pola Kemeja Pria di Fase E SMK Negeri 1 Sooko - Ratu Azani Ridwan; Peppy Mayasari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aimed to: 1) determine the feasibility level of the tutorial video based on assessments of material expert, media expert, and language expert; and 2) determine students learning outcomes after using the tutorial video on making a men’s shirt pattern. This study employed a Research and Development (R&D) method using the ADDIE development model, which consist of the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation questionnaire and students performance test. The data were analyzed using descriptive quantitative by calculating the average validation score, and the percentage of learning mastery. The result showed that the tutorial video on making a men’s shirt pattern obtained a material feasibility score of 3.97, a media feasibility score of 3.97, and a language feasibility score of 3.80. The overall average feasibility score of the tutorial video was 3.90, which falls into the “very feasible” category for implementation. Meanwhile, student’s learning outcomes based on classical mastery reached 84.85%. Based on these result, the tutorial video on making a men’s shirt pattern was declared feasible and suitable for use in learning.